Impact of face trustworthiness on approach-avoidance behavior of adolescents with varied social anxiety traits - Yuan Yao; Zhuqing Wang (BMC Psychology)
Abstract Approach/avoidance behavior is a basic human behavior pattern. However, more recent studies have demonstrated that this behavior pattern greatly differs among individuals. This heterogeneity has promoted research on exploring the predictive value of individual differences. Based on Person-Context Interaction Theory, the current study focused on the impact of face trustworthiness on adolescents’ approach/avoidance behavior with varied social anxiety traits. Results revealed that the avoidance behavior of highly anxiety individuals was affected by face trustworthiness, while in contrast, individuals with low levels of anxiety were only affected by face trustworthiness in their approach behavior. This indicates that adolescents tend to be more responsive to external influences in behaviors where they have greater proficiency, whereas external factors have a less significant impact on behaviors in which they lack skill. Results were also interpreted in terms of two independent social motivations, which may benefit the development of adolescents’ interpersonal relationships and the solution of extended problems caused by social problems.